Penerapan Metode Inquiry pada Pelajaran Pendidikan Agama Islam Materi Asmaul Husna dengan Media Gambar - Samania Samania (GHIROH, 2022)
This article focuses on regulating the feelings and attitudes of Indonesian students in PAI learning the Asmaul Husna material. This study aims to investigate the extent to which Junior High School students in Bintan Regency can improve their learning outcomes through the inquiry method. To answer this question, this study uses action research. This research lasted for three months in which students were given an action in the form of a test. The results of the data analysis showed that students showed less learning outcomes than the KKM before the action but showed a more positive improvement as a result of their learning after applying the inquiry method with picture media to the Asmaul Husna material. This study offers pedagogical implications for PAI teachers and suggestions for future researchers.